Health-related quality of life after maxillectomy: obturator rehabilitation compared with flap reconstruction. Issue 8 (October 2016) - Breeze, J.; Rennie, A.; Morrison, A.; Dawson, D.; Tipper, J.; Rehman, K.; Grew, N.; Snee, D.; Pigadas, N.
Abstract: Health-related quality of life (QoL) reported by patients has the potential to improve care after ablative surgery of the midface, as existing treatment algorithms still generally revolve around outcomes assessed traditionally only by clinicians. Decisions in particular relate to reconstruction with a flap compared with rehabilitation with an obturator, the need for adjuvant treatment, and morbidity related to the size of the defect. We prospectively collected health-related QoL assessments for 39 consecutive patients treated by maxillectomy between 01 January 2010 and 31 December 2014 using the University of Washington Quality of Life Questionnaire, and who had a mean (SD) duration of follow-up of 14 (4). We made sub-group analyses using paired t tests and analysis of variance (ANOVA) to compare reconstruction with a flap with rehabilitation with obturators, size of the vertical defect, and whether adjuvant treatment with radiotherapy or chemoradiotherapy adversely affected it. Overall there was a significant decrease in health-related QoL after treatment compared with before (p < 0.001), but there was no significant difference in the effects of any of the paired reconstructive and rehabilitation treatments on it. Obturators remain an important option for rehabilitation in selected patients in addition to reconstruction with a flap. We found that neither increasing the size of the vertical defect (in an attempt to ensure clear margins) nor the use of postoperative radiotherapy seemed to have any adverse effect on QoL. More patients are required before we can conclude that the potential survival benefits of such measures may outweigh any adverse effects.